2012
DOI: 10.1681/asn.2011101034
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Urinary Albumin Fragments Does Not Require Proximal Tubular Uptake

Abstract: Urinary albumin excretion is an important diagnostic and prognostic marker of renal function. Both animal and human urine contain large amounts of albumin fragments, but whether these fragments originate from renal tubular degradation of filtered albumin is unknown. Here, we used mice with kidneys lacking megalin and cubilin, the coreceptors that mediate proximal tubular endocytosis of albumin, to determine whether proximal tubular degradation of albumin forms the detectable urinary albumin fragments. After in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 32 publications
0
27
4
Order By: Relevance
“…14,15,19,30 The small fractions of labeled albumin in the plasma (detailed above) may be yet another reason for the physiologically unrealistic high sieving values presented by other groups. As reported in the work by Weyer et al, 29 low-molecular weight albumin fragments amounting to 2% of the total albumin in serum would cause the albumin GSC to be grossly overestimated (0.0206 instead of 0.0006).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…14,15,19,30 The small fractions of labeled albumin in the plasma (detailed above) may be yet another reason for the physiologically unrealistic high sieving values presented by other groups. As reported in the work by Weyer et al, 29 low-molecular weight albumin fragments amounting to 2% of the total albumin in serum would cause the albumin GSC to be grossly overestimated (0.0206 instead of 0.0006).…”
Section: Discussionmentioning
confidence: 79%
“…A very recent report by Weyer et al 29 found small amounts of low-molecular weight fragments of injected labeled albumin in the plasma of mice. Because these small fragments can be readily filtered in the kidney, they may help explain the higher albumin GSC results.…”
Section: Discussionmentioning
confidence: 94%
“…35 More recently, it could be shown that albumin degradation products typically found in the urine 36 are not formed within proximal tubular cells of the kidney but rather, are formed in other tissues. 37 By two-photon microscopy, fluorescently labeled albumin was observed within endocytotic vesicles of proximal tubules in vivo. 38 Some of the vesicles fused with the basolateral membrane during the observation period, indicating a transcytosis mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…21 PTCs are specialized to capture ultrafiltrated proteins by apical receptor-mediated endocytosis (ARME) through abundantly expressed, rapidly recycling multiligand tandem receptors, megalin, and cubilin. 22 Megalin-and cubilin-knockout mice show defective PTC endocytosis and urinary loss of ultrafitrated plasma proteins [23][24][25][26] and lysosomal enzymes. 27,28 Although defective ARME caused by loss of megalin/cubilin was a possible explanation for proteinuria of cystinotic patients, normal immunolabeling of megalin/cubilin was reported in an end stage cystinotic kidney despite massive proteinuria, calling attention to glomerular leakage.…”
mentioning
confidence: 99%